2021
DOI: 10.1186/s41687-021-00392-0
|View full text |Cite
|
Sign up to set email alerts
|

Structural validity of the Arabic version of the disabilities of the Arm, Shoulder and Hand (DASH) using Rasch measurement model

Abstract: Background The disabilities of the arm, shoulder and hand (DASH) is a commonly used region-specific patient-reported outcome measure (PROM) that quantify upper extremity function (activity limitation) and symptoms. Current evidence suggests that measurement properties of the adapted versions of the DASH are not sufficiently examined. The Arabic DASH has evidence supporting its internal consistency, test–retest reliability, construct validity and responsiveness. On the other hand, the validity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…There are 17 language versions with evidence of the assessment of structural validity of which the following language versions had evidence of EFA: Chinese, 33 French, 34 German, 35 Igbo, 36 Japanese, 37 Nepali 38 Persian, 39 Portuguese (Brazil), 40 Taiwanese 41 and Yoruba. 42 The Arabic, 43 Dutch, 44 English (British) 45,46 and Finish 47 language versions have evidence of structural validity through Rasch analysis. In a separate study from authors from the Netherlands, CFA was conducted using the Dutch DASH questionnaire.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are 17 language versions with evidence of the assessment of structural validity of which the following language versions had evidence of EFA: Chinese, 33 French, 34 German, 35 Igbo, 36 Japanese, 37 Nepali 38 Persian, 39 Portuguese (Brazil), 40 Taiwanese 41 and Yoruba. 42 The Arabic, 43 Dutch, 44 English (British) 45,46 and Finish 47 language versions have evidence of structural validity through Rasch analysis. In a separate study from authors from the Netherlands, CFA was conducted using the Dutch DASH questionnaire.…”
Section: Resultsmentioning
confidence: 99%
“…Of the studies that investigated the factor structure of the DASH questionnaire, eight studies concluded that the questionnaire holds a single factor structure. 33,37,39,41,43,44,46,48 One study supported a two factor structure, 36 five a three factor structure, 35,40,[49][50][51] one a four factor structure, 38 one a five factor structure 34 and one a seven factor structure. 42…”
Section: Structural Validitymentioning
confidence: 99%
“…The decision to conduct CFA towards confirming a one-factor structure in the Afrikaans for the Western Cape DASH follows best practice in accordance with the COSMIN guidelines [ 25 , 34 ], and in line with previous evidence supporting the unidimensionality of this instrument [ 17 – 23 , 35 , 36 ]. Several studies on the structural validity of the DASH questionnaire following translation and cross-cultural adaptation however did not support unidimensionality [ 37 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Factor analysis of the Nigerian Igbo version of the DASH questionnaire also revealed a two-factor structure [ 42 ]. This study from Nigeria is one of few (excluding the current study) reporting on language versions from the African continent and to our knowledge the only to report a two-factor model [ 17 , 41 , 42 , 48 , 49 ]. Our findings were similar to that of Ibikunle et al (Igbo DASH) with their Factor 1 (strength based) also comprising of items 1–21 explaining 58.5% of the variance and Factor 2 (pain based) items 22–30 explaining 6.8% of the variance [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation